Relationships between plasma fatty acids in adults with mild, moderate, or severe COVID-19 and the development of post-acute sequelae - Stromberg, Sophia; Baxter, Bridget A.; Dooley, Gregory; LaVergne, Stephanie M.; Gallichotte, Emily; Dutt, Taru; Tipton, Madison; Berry, Kailey; Haberman, Jared; Natter, Nicole; Webb, Tracy L.; McFann, Kim; et al. (Frontiers in Nutrition, 2022)
Background SARS-CoV-2 has infected millions across the globe. Many individuals are left with persistent symptoms, termed post-acute sequelae of COVID-19 (PASC), for months after infection. Hyperinflammation in the acute and convalescent stages has emerged as a risk factor for poor disease outcomes, and this may be exacerbated by dietary inadequacies. Specifically, fatty acids are powerful inflammatory mediators and may have a significant role in COVID-19 disease modulation. Objective The major objective of this project was to pilot an investigation of plasma fatty acid (PFA) levels in adults with COVID-19 and to evaluate associations with disease severity and PASC. Methods and procedures Plasma from adults with (N = 41) and without (N = 9) COVID-19 was analyzed by gas chromatography-mass spectrometry (GC-MS) to assess differences between the concentrations of 18 PFA during acute infection (≤14 days post-PCR + diagnosis) in adults with varying disease severity. Participants were grouped based on mild, moderate, and severe disease, alongside the presence of PASC, a condition identified in patients who were followed beyond acute-stage infection (N = 23). Results Significant differences in PFA profiles were observed between individuals who experienced moderate or severe disease compared to those with mild infection or no history of infection. Palmitic acid, a saturated fat, was elevated in adults with severe disease (p = 0.04), while behenic (p = 0.03) and lignoceric acid (p = 0.009) were lower in adults with moderate disease. Lower levels of the unsaturated fatty acids, γ-linolenic acid (GLA) (p = 0.03), linoleic (p = 0.03), and eicosapentaenoic acid (EPA) (p = 0.007), were observed in adults with moderate disease. Oleic acid distinguished adults with moderate disease from severe disease (p = 0.04), and this difference was independent of BMI. Early recovery-stage depletion of GLA (p = 0.02) and EPA (p = 0.0003) was associated with the development of PASC. Conclusion Pilot findings from this study support the significance of PFA profile alterations during COVID-19 infection and are molecular targets for follow-up attention in larger cohorts. Fatty acids are practical, affordable nutritional targets and may be beneficial for modifying the course of disease after a COVID-19 diagnosis. Moreover, these findings can be particularly important for overweight and obese adults with altered PFA profiles and at higher risk for PASC. Clinical trial registration [ClinicalTrials.gov], identifier [NCT04603677].